PERNCANAAN PENJADWALAN KANTOR GEDUNG PT GRESIK JASATAMA DENGAN METODE FUZZY LOGIC APLICATION FOR SCHEDULING (FLASH) - ARIF MIFTAKUL HUDA (Matrik : Jurnal Manajemen dan Teknik Industri Produksi, 2018)
CV. Mukti Jaya Abadi is a company in the General Contractor and Supplier, for these companies in the project schedule based on the analysis of the head of the project and project estimator, Result there is uncertainty about the project completion time. Therefore it takes the right approach to determine the time of the project, in this case the fuzzy method is able to provide a good completion to the things that are uncertain. Fuzzy Logic Application for Scheduling (FLASH) is an appropriate method to accommodate uncertainty. FLASH does not require statistical data but only qualitative observation. The resultsobtained showtheprojectcanis overcomerange119daysto221dayswiththe mostlikelytime of163daysto170daysdefuzzyficationvalue.